Предмет: Алгебра,
автор: marina7258
(с-4)^2 - (3-с)^2 спростити вираз
Ответы
Автор ответа:
2
Первый способ :
(c - 4)² - (3 - c)² = c² - 8c + 16 - (9 - 6c + c²) = c² - 8c + 16 - 9 + 6c - c² =
= 7 - 2c
Второй способ :
(c - 4)² - (3 - c)² = (c - 4 - 3 + c)(c - 4 + 3 - c) = (2c - 7) * (- 1) = 7 - 2c
Похожие вопросы
Предмет: Математика,
автор: borylkoivan23rus
Предмет: История,
автор: gustav22820
Предмет: История,
автор: alnurerk
Предмет: Математика,
автор: катя2963
Предмет: Математика,
автор: Аноним